How can a five star hotel increase its luxury status: the case of intercontinental Lisbon - Cunha, Andreia Filipa Ribeiro da (2017)
With luxury consumption increasingly changing from the notion of owning to experiencing, the luxury hospitality sector is blossoming internationally. However, while defining luxury is not an easy process, understanding what constitutes a luxury hotel becomes even more challenging. InterContinental Hotels & Resorts presents itself as one of the largest international luxury hotel chains. Nonetheless, the research conducted over this Work Project revealed that InterContinental Lisbon is currently not perceived as a luxury hotel nor fulfilling the luxury business models proposed in the literature. This project offers InterContinental Lisbon relevant insights to increase its luxury status, matching its image with the corporate brand identity of InterContinental Hotels & Resorts. Recommendations are also drawn for other five star hotels in Lisbon.